Dizzy - O'Donnell, Peter (New York : Scholastic, 1992)
Left behind at the airport, an elephant searches for his friends in what seems to be a concrete jungle.
School Library Journal
Publisher's Weekly
Horn Book
5.1
K-3
Keywords: Elephants -- Fiction; Airports -- Fiction; Elephants -- Fiction; Airports -- Fiction